Description of Management in Professional Development of Civil Service Learning at SPNF Studio Learning Activities in Padang Panjang City - Alfi Rahmawati; Irmawita Irmawita; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by professional tutors in carrying out their main duties and functions at SPNF, a Learning Center for Padang Panjang City. The purpose of this study is to describe  (1) motivation, (2) briefing, and (3) supervision in the framework of management by the SKB Head. This type of research is a quantitative descriptive. The study population amounted to 12 people who were also respondents to the study. Data collection techniques used were questionnaires, with data collection tools using questionnaires. The data analysis technique uses the percentage formula. The results of the study showed that (1) the direction in improving the professional learning service was categorized quite high, (2) motivating the improvement of professional learning services is categorized as quite high, and (3) supervision in improving professional learning is categorized quite high. Suggestions that leaders can maintain management both from aspects of motivation, direction, and supervision.Keywords: Management, Briefing, Direction, Supervision